Exploring The Facts of Teaching Technologies for Accounting Students in The Digital Era - Angela, Leliana Maria; Susanti, Wahyu Febri Eka; Rakhmawati, Dewi; Amelia, Verra Rizki (Universitas Negeri Padang, 2025)
Accounting education has been significantly impacted by the digital age, especially regarding the ability to use electronic technology in the accounting industry. However, we face the pressing need to close the gap between accounting education and technical advancements in accounting reporting. Multimedia interactive learning resources Yes, a lot has been created, but frequently without considering the curriculum and user needs. This study offers a viewpoint on technology acceptability in the curriculum provided to aspiring accountants using the Technology acceptability Model (TAM) approach. This study employs a quantitative approach, gathering information using primary sources, specifically a survey. research uses a quantitative method by collecting data through primary data, namely a questionnaire. There are a total of 44 questions consisting of 13 questions to explain the exploration of students' knowledge and skills, and 31 questions to explain the prediction of individuals' ability to adapt and use new technologies. According to the study's findings, students' opinions about how beneficial and simple technology is to use are heavily impacted by outside variables including prior educational experiences. A favorable attitude toward students' intention to use technology in their learning activities will encourage them. But there are still some issues that need to be resolved, like students' inability to use specific software and their lack of interest in learning new technology. The study's findings suggest that outside variables, such as past educational experiences, significantly impact how students view the usefulness and usability of technology.